If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = 11x + -29 Reorder the terms: -5 + 3x = 11x + -29 Reorder the terms: -5 + 3x = -29 + 11x Solving -5 + 3x = -29 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -5 + 3x + -11x = -29 + 11x + -11x Combine like terms: 3x + -11x = -8x -5 + -8x = -29 + 11x + -11x Combine like terms: 11x + -11x = 0 -5 + -8x = -29 + 0 -5 + -8x = -29 Add '5' to each side of the equation. -5 + 5 + -8x = -29 + 5 Combine like terms: -5 + 5 = 0 0 + -8x = -29 + 5 -8x = -29 + 5 Combine like terms: -29 + 5 = -24 -8x = -24 Divide each side by '-8'. x = 3 Simplifying x = 3
| 8+27x+6-14x=5+10x+9+3x | | t-47=-35 | | 9p+13=3p-5 | | 3t-47=-35 | | y^2=x | | y(2+5)-13=64 | | x^2+4x+1= | | 9m+5=29-3m | | 92-t=37 | | 3.14*3.14+b^2=30 | | 101-7x=11x+19 | | 3*3*3+b^2=30 | | (4x-1)(7x+8)=0 | | 3*3*3+b^2=25 | | 3*3+b^2=25 | | 60=3t-13t | | 95-3x=3x+17 | | 5x-14=51 | | 2y-6=-5 | | 95-3x=3x | | 4x=8-(-16) | | -14-3=7-10x | | 2w-4w=-12 | | 2(p+1)=3(p-1) | | 9+b^2=25 | | y=-13 | | a^2+b^2=25 | | -6-5=-7+x | | 3x*5x= | | 14-45=3(x-3)-7 | | 12=2x+4x | | 3x*6x^2= |